2022
DOI: 10.1002/ptr.7454
|View full text |Cite
|
Sign up to set email alerts
|

The role of Pycnogenol in the control of inflammation and oxidative stress in chronic diseases: Molecular aspects

Abstract: The prevalence of chronic diseases has increased significantly with the rising trend of sedentary lifestyles, reduced physical activity, and dietary modifications in recent decades. Inflammation and oxidative stress play a key role in the pathophysiology of several chronic diseases, such as type II diabetes, cardiovascular diseases, and hepatic conditions. Therefore, reducing inflammation and oxidative stress may be beneficial in the prevention and treatment of various chronic disorders. Since chronic diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 161 publications
0
16
0
Order By: Relevance
“…Pycnogenol ® ’s unique composition of bioactive substances with diverse biological targets explains its efficacy on a broad range of human health conditions. The mechanisms of action of Pycnogenol ® were explored in several in vitro , in vivo and in clinical studies over the years ( 27 ). Randomized double-blind placebo-controlled (RDP) clinical trials help clarify and confirm some of the mechanisms of action of Pycnogenol ® at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pycnogenol ® ’s unique composition of bioactive substances with diverse biological targets explains its efficacy on a broad range of human health conditions. The mechanisms of action of Pycnogenol ® were explored in several in vitro , in vivo and in clinical studies over the years ( 27 ). Randomized double-blind placebo-controlled (RDP) clinical trials help clarify and confirm some of the mechanisms of action of Pycnogenol ® at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Pycnogenol ® has been shown to have four main effects being its antioxidative effects ( 9 14 ), its anti-inflammatory action ( 15 18 ), its positive impact on blood circulation ( 9 , 19 24 ) and its reinforcing effects on the extracellular matrix ( 25 , 26 ) ( Figure 1 ). Mainly through these mechanisms ( 27 ), Pycnogenol ® supplementation has been shown in RDP human clinical trials to beneficially affect cardiovascular health ( 9 , 11 , 12 , 20 22 , 28 – 31 ), chronic venous insufficiency ( 32 , 33 ), cognition ( 13 , 14 , 34 39 ), joint health ( 40 42 ), skin health ( 43 , 44 ), eye health ( 45 , 46 ), women’s health ( 12 , 47 , 48 ), respiratory health and allergies ( 49 51 ), oral health ( 52 ) and sports performance ( 53 – 56 ) ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, roughly 160 clinical studies with over 10,000 participants have been reported for Pycnogenol ® . The results suggested a beneficial impact in various chronic disease states, particularly when inflammation and/or oxidative stress contributed to the pathophysiology ( 9 , 10 ). Documented clinical effects prompted deeper investigations of underlying cellular mechanisms and identification of relevant bioactive molecules.…”
Section: Introductionmentioning
confidence: 96%
“…The emergence of complementary therapies appears to be a vital method for physicians to be aware of the risks and advantages of these options [ [9] , [10] , [11] , [12] ]. Amongst various treatment strategies, the use of natural products and minerals seems to be safe, efficient and found naturally in foods [ [13] , [14] , [15] , [16] , [17] ]. It has been shown that minerals such as selenium, magnesium, calcium and chromium can play an important role in cardiovascular health [ 13 , [18] , [19] , [20] ].…”
Section: Introductionmentioning
confidence: 99%